Teachers’ professional development in school: A review study - May Britt Postholm (Cogent Education, 2018)
This review study includes 43 articles from 2016 and 2017 focusing on teachers’ professional development, as guided by the following twofold research question: “What characterizes teachers’ professional development in school, and how does this development influence school improvement?” The review indicates that teachers’ learning processes need to be developed if they are to lead to school improvement. It is not enough for researchers simply to study learning processes in schools; they must also conduct formative intervention studies. Ultimately, while conducting research on these processes, researchers should provoke and sustain an expansive transformation process led by and owned by practitioners—leaders and teachers in the whole school. Findings suggest that more research is needed to show how outside resource persons, such as researchers, can contribute to school development in collaboration with teachers and school leaders at work.